2022
DOI: 10.1097/hjh.0000000000003178
|View full text |Cite
|
Sign up to set email alerts
|

Role of plasma extracellular vesicles in prediction of cardiovascular risk and alterations in response to statin therapy in hypertensive patients

Abstract: Background:Rapid and accurate new biomarkers to predict risk of cardiovascular disease (CVD) are essential. The utility of extracellular vesicles in predicting the CVD risk is postulated, yet it remains unknown whether their expression is altered in response to statin therapy.Methods:We performed in-vitro studies with human umbilical vein endothelial cells (HUVEC) and vascular smooth muscle cells (hVSMC), and conducted a nested case–control study (nCCS) in hypertensive patients (n = 40) randomized to either at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…Although a number of EVs-based biomarkers have entered clinical trials, covering the fields of tumors [ 133 , 134 ], cardiovascular diseases [ 135 ], and even infectious diseases [ 136 ], there is no relevant research in the field of OA. EVs have been used in clinical studies to diagnose diseases [ 137 ], predict progression [ 133 ], and evaluate efficacy and prognosis [ 135 , 138 , 139 ]. These studies further demonstrate the potential of EVs as biomarkers.…”
Section: 'Supervisor'——evs As a Biomarker Of Oamentioning
confidence: 99%
“…Although a number of EVs-based biomarkers have entered clinical trials, covering the fields of tumors [ 133 , 134 ], cardiovascular diseases [ 135 ], and even infectious diseases [ 136 ], there is no relevant research in the field of OA. EVs have been used in clinical studies to diagnose diseases [ 137 ], predict progression [ 133 ], and evaluate efficacy and prognosis [ 135 , 138 , 139 ]. These studies further demonstrate the potential of EVs as biomarkers.…”
Section: 'Supervisor'——evs As a Biomarker Of Oamentioning
confidence: 99%
“…With the occurrence of CVD, circulating EVs of platelets and endothelial cells, among other sources, are significantly higher than in normal persons [ 297 , 298 ]. Oggero et al [ 299 ] during 3.5 years of follow-up (median) showed that in a population at risk for major adverse cardiovascular event or death (MACE) and receiving atorvastatin therapy (compared with controls and placebo, respectively), the biology of plasma-derived EVs was significantly different in size, level, and surface characteristics. MACE patients had preceding higher levels of CD14 + and CD14 + /CD41 + EVs, and higher CD14 + extracellular vesicles were associated with a 3.7-fold increased risk of MACE on matched analysis [ 299 ].…”
Section: Circulating Evs As Potential Predictors In Cardiovascular Ev...mentioning
confidence: 99%
“…Oggero et al [ 299 ] during 3.5 years of follow-up (median) showed that in a population at risk for major adverse cardiovascular event or death (MACE) and receiving atorvastatin therapy (compared with controls and placebo, respectively), the biology of plasma-derived EVs was significantly different in size, level, and surface characteristics. MACE patients had preceding higher levels of CD14 + and CD14 + /CD41 + EVs, and higher CD14 + extracellular vesicles were associated with a 3.7-fold increased risk of MACE on matched analysis [ 299 ]. Patients treated with atorvastatin had both reduced size of extracellular vesicles and the proportion of CD146 + extracellular vesicles [ 299 ].…”
Section: Circulating Evs As Potential Predictors In Cardiovascular Ev...mentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of circulating EVs increases in thrombotic, inflammatory or infectious diseases, and their molecular content changes with disease progression, reflecting the activation state of the involved cells and/or compartment [ 1 ]. Therefore, circulating EVs have emerged as both surrogate biomarkers of disease prognosis and potential pharmacological targets due to them being paracrine carriers able to influence target cells [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%